Chromosome-level genome of the shining chafers Kibakoganea tamdaoensis (Coleoptera: Scarabaeidae: Rutelinae) - Rongrong Shen; Terrence Sylvester; Qiang Ding; Xinwen Yang; Yijie Tong; Ning Liu; Can Wang; Yansong Xiao; Chunyang Huang; Shaolong Wu; Ming Bai (Scientific Data)
Abstract The beetle subfamily Rutelinae (shining leaf chafers) in the family Scarabaeidae is famous for its colorful body and phytophagous habitat. Among these shining leaf chafers, Kibakoganea tamdaoensis Miyake et Muramoto, 1992 is one with ornamental value because of their enlarged and horn-like mandibles. Here we generated high-quality genome assembly of KTAMD, integrating PacBio HiFi and Hi-C, and annotated with RNA sequence data. The resulting assembly is 605.37 Mb, of which 96.09% is anchored into 10 chromosomes. The scaffold N50 is 54.00 Mb, and BUSCO completeness is 96.6%. Repetitive elements span 49.43% of the genome. Our annotation pipeline identified 984 noncoding RNAs and predicted 12,945 protein-coding genes in the genome (96.40% BUSCO completeness). As the chromosome-scale genome from the subfamily Rutelinae, the KTAMD genome provides important new insights into scarabae genome evolution and provides a new vantage point from which to study the evolution of specialized beetles.